PENANGANAN ANAK BERKESULITAN BELAJAR BERBASIS AKOMODASI PEMBELAJARAN - Sari Rudiyati (Universitas Negeri Yogyakarta, 2010)
The general objective of this study is to create a model of treatment for children with learning difficulties (CLD) by accommodation-based learning with elements: (1) material and techniques of instruction; (2) assignment and evaluation; (3) time demand and schedules; and (4) evironment of learning. The specific objective of this study is to create an accommodation-based treatment manual for CLD to: (1) provide educational services and instruction for CLD; (2) improve teachers knowledge and awareness of the importance of learning accomodation for CLD; and (3) increase the learning avchievement of CLD. This study is research and development. Data collection is conducted through the Delphi technique, focus group discussion (FGD), questionnaire, observation, interview, and documentation. Data analysis is descriptive. The findings show that: (1) In the first years: (a) CLD treatment has not been adequately performed; it means that the exact solution has not been found out in learning accommodation for CLD; (b) teachers perception and expectation on learning problems of CLD have not been quite positive; (c) the prototype of CLD treatment based on learning accommodation has been limitedly to test-driven and can be developed as a model of treatment for CLD in the elementary school. Its implementation is based on a manual of learning accommodation application for CLD. (2) In the second years, the model and product have been validated through the main field testing and operational field testing; and stated as a fit and effective model of CLD treatment in the elementary school. The effectiveness of the accommodation learning treatment is evident from indicators that the elementery school teachers have applied the model and product found in the manual books for CLD instructional flexibilities. In addition, the application of the model has improved the (a) learning motivation; (b) social interaction; and (c) academic achievement of CLD